2011
DOI: 10.1128/jvi.00378-11
|View full text |Cite
|
Sign up to set email alerts
|

RAB11A Is Essential for Transport of the Influenza Virus Genome to the Plasma Membrane

Abstract: Influenza A virus assembly is a complex process that requires the intersection of pathways involved in transporting viral glycoproteins, the matrix protein, and viral genomes, incorporated in the viral ribonucleoprotein (vRNP) complex, to plasma membrane sites of virion formation. Among these virion components, the mechanism of vRNP delivery is the most incompletely understood. Here, we reveal a functional relationship between the cellular Rab11 GTPase isoform, RAB11A, and vRNPs and show that RAB11A is indispe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
213
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(249 citation statements)
references
References 53 publications
17
213
0
1
Order By: Relevance
“…In fact, Rab11 distribution changes with infection from discrete puncta to enlarged structures (Amorim et al, 2011;Chou et al, 2013;Eisfeld et al, 2011). This conclusion originated from confocal microscopy analyses from four independent studies, using different systems, including a mini-replicon system that was devoid of segments 4 and 6 (Amorim et al, 2011), and infection with wild-type viruses (Avilov et al, 2012a;Eisfeld et al, 2011;Momose et al, 2011). To determine the viral factors that provoke changes in the recycling compartment, we quantified the changes in Rab11 distribution during infection (Fig.…”
Section: Iav Infection Induces Alterations In Rab11a Distribution Lementioning
confidence: 99%
See 1 more Smart Citation
“…In fact, Rab11 distribution changes with infection from discrete puncta to enlarged structures (Amorim et al, 2011;Chou et al, 2013;Eisfeld et al, 2011). This conclusion originated from confocal microscopy analyses from four independent studies, using different systems, including a mini-replicon system that was devoid of segments 4 and 6 (Amorim et al, 2011), and infection with wild-type viruses (Avilov et al, 2012a;Eisfeld et al, 2011;Momose et al, 2011). To determine the viral factors that provoke changes in the recycling compartment, we quantified the changes in Rab11 distribution during infection (Fig.…”
Section: Iav Infection Induces Alterations In Rab11a Distribution Lementioning
confidence: 99%
“…Recently, it has been shown that IAV vRNPs attach to Rab11 vesicles after nuclear export, and depletion of the two isoforms of Rab11 (Rab11a and Rab11b, henceforward Rab11 refers to both isoforms) impacts negatively on viral production (Amorim et al, 2011;Avilov et al, 2012b;Eisfeld et al, 2011;Momose et al, 2011). Rab11 is the master regulator of the recycling endosome, described as a web of tubulovesicular membranes (Mobius et al, 2003), that deliver endocytosed proteins and lipids, as well as material segregated from the trans-Golgi network, to the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Some host actin-binding proteins, such as Rab 11 and myosin, are essential for IAV genome transport to the plasma membrane and budding formation [30,31,32,33]. The major actin-depolymerizing factor (ADF)/cofilin isoform, Cofilin-1 is primarily responsible for dynamic actin cytoskeletal reorganization [15], and functions depending on its local concentration of active form relative to actin: relative low concentrations of active cofilin to actin favor severing, whereas high concentrations of cofilin favor nucleating actin assembly [34].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated through the use of live imaging microscopy that, upon entering the cytoplasm, vRNP complexes associate with a pericentriolar recycling endosome marker called Rab11, which is involved in endosomal recycling and trafficking [130]. The accumulation of vRNPs at the microtubule-organizing center after nuclear export, allows them to interact with Rab11-positive recycling endosomes and migrate along microtubules to the sites of budding at the apical surface of the plasma membrane [131][132][133].…”
Section: Unexpected Delivery: Nuclear Export Of Viral Mrna and The Vrnpmentioning
confidence: 99%